Cyclic Behavior of Slender Shear Walls with Ultra High Performance Fiber Reinforcement Concrete Overlays - Geralda Nurry Arifa; Aniendhita Rizki Amalia; Yuyun Tajunnisa (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2025)
Shear walls serve as the primary structural elements for resisting lateral loads induced by earthquakes; however, slender shear walls remain susceptible to shear failure and buckling, particularly in structures designed according to older design codes. One strengthening technique that has gained increasing attention is the application of Ultra-High Performance Fiber Reinforced Concrete (UHPFRC) overlays, which offer high strength and effective crack control capabilities. This study aims to analyze the cyclic behavior of slender shear walls strengthened with a two-layer UHPFRC overlay with a total thickness of 40 mm using a finite element method based on the Concrete Damage Plasticity (CDP) model implemented in Abaqus. The numerical model is validated using experimental data from conventional reinforced concrete shear walls and UHPFRC-strengthened shear walls by comparing force–displacement responses, hysteresis curves, and tensile damage (Damage) distributions. The validation results indicate that the numerical model accurately captures the structural response, as evidenced by the close agreement in maximum displacement and damage mechanisms, with displacement differences of 2.97% for the conventional shear wall and 0.18% for the UHPFRC-strengthened shear wall. Parametric analysis shows that the UHPFRC overlay significantly increases the maximum load capacity from 328.22 kN to 525.37 kN, enhances the initial stiffness and first-yield capacity, and reduces the maximum displacement from 127.79 mm to 112.50 mm. Furthermore, the UHPFRC-strengthened shear wall exhibits a more stable post-peak response, fuller hysteresis loops, higher energy dissipation capacity, and more localized and gradually developing tensile damage compared to the conventional shear wall. These results demonstrate that a 40 mm-thick two-layer UHPFRC overlay effectively improves the shear capacity, cyclic stability, and seismic resistance of slender shear walls.